Artificial Intelligence and Computational Intelligence International Conference, AICI 2010, Sanya, China, October 23-24, 2010, Proceedings, Part I - Wang, Fu Lee.; Deng, Hepu.; Gao, Yang.; Lei, Jingsheng (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The 2010 International Conference on Artificial Intelligence and Computational Intelligence (AICI 2010) was held October 23–24, 2010 in Sanya, China. The AICI 2010 received 1,216 submissions from 20 countries and regions. After rigorous reviews, 105 high-quality papers were selected for publication in the AICI 2010 proceedings. The acceptance rate was 8%. The aim of AICI 2010 was to bring together researchers working in many different areas of artificial intelligence and computational intelligence to foster the exchange of new ideas and promote international collaborations. In addition to the large number of submitted papers and invited sessions, there were several internationally well-known keynote speakers. On behalf of the Organizing Committee, we thank Hainan Province Institute of Computer and Qiongzhou University for its sponsorship and logistics support. We also thank the members of the Organizing Committee and the Program Committee for their hard work. We are very grateful to the keynote speakers, invited session organizers, session chairs, reviewers, and student helpers. Last but not least, we thank all the authors and participants for their great contributions that made this conference possible.
Applications of Artificial Intelligence -- Application of RBF Neural Network in Short-Term Load Forecasting -- Efficient Large Image Browser for Embedded Systems -- Formalizing Ontology-Based Hierarchical Modeling Process of Physical World -- Automated Problem Solving -- Satisfiability Degree Analysis for Transition System -- Research on Optimization Design of Bottom Angle of Drag-Reducing Structure on the Riblets Surface -- Towards Analysis of Semi-Markov Decision Processes -- Automatic Programming -- Stability of Equilibrium Solution and Periodical Solution to Cohen-Grossberg Neural Networks -- Exponential Synchronization of Delayed Fuzzy Cohen-Grossberg Neural Networks with Reaction Diffusion Term -- Magnetic Field Extrapolation Based on Improved Back Propagation Neural Network -- Sparse Deep Belief Net for Handwritten Digits Classification -- Data Mining and Knowledge Discovering -- Multisensor Image Fusion Using a Pulse Coupled Neural Network -- Real-Time Performance Reliability Assessment Method Based on Dynamic Probability Model -- Decomposing Data Mining by a Process-Oriented Execution Plan -- An Efficient Distributed Subgraph Mining Algorithm in Extreme Large Graphs -- Spatio-Temporal Clustering of Road Network Data -- A Sampling Based Algorithm for Finding Association Rules from Uncertain Data -- Distributed AI and Agents -- Multi-agent System Collaboration Based on the Relation-Web Model -- Research on A Novel Multi-Agents Dynamic Cooperation Method Based on Associated Intent -- Expert and Decision Support Systems -- Automobile Exhaust Gas Detection Based on Fuzzy Temperature Compensation System -- Technical Efficiency Analysis of New Energy Listed Companies Based on DEA -- Fuzzy Logic and Soft Computing -- Research on Differential Evolution Algorithm Based on Interaction Balance Method for Large-Scale Industrial Processes of Fuzzy Model -- Fuzzy Control System Design for Solar Energy with PCM Tank to Fresh Air Conditioning -- Intelligent Information Fusion -- An Efficient Method for Target Extraction of Infrared Images -- Second Order Central Difference Filtering Algorithm for SINS/GPS Integrated Navigation in Guided Munitions -- Adaptive Signal Processing for ARX System Disturbed by Complex Noise -- Abstraction for Model Checking the Probabilistic Temporal Logic of Knowledge -- Intelligent Scheduling -- Research on Double-Objective Optimal Scheduling Algorithm for Dual Resource Constrained Job Shop -- MDA Compatible Knowledge– Based IS Engineering Approach -- Intelligent Signal Processing -- ARIMA Signals Processing of Information Fusion on the Chrysanthemum -- Noise Uncertainty Study of the Low SNR Energy Detector in Cognitive Radio -- Machine Learning -- A Realtime Human-Computer Ensemble System: Formal Representation and Experiments for Expressive Performance -- A New Smooth Support Vector Machine -- Convergence of GCM and Its Application to Face Recognition -- Designing a Multi-label Kernel Machine with Two-Objective Optimization -- Collision Detection Algorithm in Virtual Environment of Robot Workcell -- Machine Vision -- A First Step towards Hybrid Visual Servoing Control Based on Image Moments -- A Novel Motion Detection Approach for Large FOV Cameras -- Large Scale Visual Classification via Learned Dictionaries and Sparse Representation -- Semi-supervised Nearest Neighbor Discriminant Analysis Using Local Mean for Face Recognition -- Multi-agent Systems -- Decentralized Cohesive Motion Control of Multi-agent Formation in 3-Dimensional Space -- A Model for Cooperative Design Based on Multi-Agent System -- Natural Language Processing -- Scaling Up the Accuracy of Bayesian Classifier Based on Frequent Itemsets by M-estimate -- Aggressive Dimensionality Reduction with Reinforcement Local Feature Selection for Text Categorization -- Neural Networks -- 3D Shape Representation Using Gaussian Curvature Co-occurrence Matrix -- Nonlinear System Identification of Bicycle Robot Based on Adaptive Neural Fuzzy Inference System -- Transmission: A New Feature for Computer Vision Based Smoke Detection -- A Novel Features Design Method for Cat Head Detection -- Time Serial Model of Rock Burst Based on Evolutionary Neural Network -- Multilayer Perceptron Network with Modified Sigmoid Activation Functions -- Pattern Recognition -- Kernel Oblique Subspace Projection Approach for Target Detection in Hyperspectral Imagery -- Text-Independent Voice Conversion Based on Kernel Eigenvoice -- An Effective Method for SAR Automatic Target Recognition -- Semi-supervised Learning by Spectral Mapping with Label Information -- Drop Fingerprint Recognition Based on Self-Organizing Feature Map -- Nonlinear Complementarity Problem and Solution Methods -- Robotics -- A New Path Planning Method for a Shape-Shifting Robot -- Pedestrian Gait Classification Based on Hidden Markov Models -- L-Infinity Norm Minimization in the Multiview Triangulation -- Erratum -- Erratum to: An Efficient Method for Target Extraction of Infrared Images.
SpringerLink eBooks.
Keywords: Computer science; Special purpose computers; Software engineering; Computers; Algorithms; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices; Software Engineering; Simulation and Modeling; Special Purpose and Application-Based Systems